Short-Term Outcomes of Transcatheter VSD Closure Using the MFO Device at a Tertiary Cardiac Centre in Lahore: Outcomes of Transcatheter VSD Closure Using MFO Device - Ahmad, Muhammad Afzal; Asma, Touseef; Athar, Husnain; Asma, Yumna; Qasem, Faez; Rehman, Asif Ur (Pakistan Journal of Health Sciences, 2026)
Transcatheter closure is the commonly used approach to treat congenital ventricular septal defect (VSD), though local outcome data on the use of KONAR-Multi Functional Occluder (MFO) in Pakistan are scarce. Objectives: The purpose of this study was to evaluate the short-term outcomes following transcatheter VSD closure with the MFO device and to compare the results in retrograde versus the antegrade methods. Methods: Prospective observational research was carried out in the Department of Pediatric Cardiology, Punjab Institute of Cardiology, Lahore. They included patients aged between three years and thirty-one years of age who had previously experienced transcatheter VSD closure using the MFO device between January 2021 and June 2024. There were 30 patients who were enrolled, of whom 20 patients were under retrograde, and 10 patients were under antegrade. The predictors of residual shunt were determined by logistic regression. Results: Four patients (13.3) had a residual shunt at discharge, and it reduced to one (3.3) at one-month follow-up. There were three patients with aortic regurgitation in the early post-procedure period (10%). The significance of the ventricular septal defect diameter exceeding six millimeters was only significantly related to residual shunt (odds ratio 4.28, p = 0.041). There were no significant conduction changes or device embolization during hospitalization or 1-month follow-up. Conclusions: Short-term success with low complication rates was observed in both methods of Transcatheter closure of VSD with the MFO device. The results demonstrate the safety of this method within a local Pakistani tertiary care environment.